2017
DOI: 10.1371/journal.pone.0178353
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical markers of the peripheral vasoconstriction response to pain in sickle cell disease

Abstract: Painful vaso-occlusive crisis (VOC), a complication of sickle cell disease (SCD), occurs when sickled red blood cells obstruct flow in the microvasculature. We postulated that exaggerated sympathetically mediated vasoconstriction, endothelial dysfunction and the synergistic interaction between these two factors act together to reduce microvascular flow, promoting regional vaso-occlusions, setting the stage for VOC. We previously found that SCD subjects had stronger vasoconstriction response to pulses of heat-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The height of the PPG pulses was extracted (photoplethysmograph amplitude [PPGamp]), followed by the same pre-processing steps for the LDF signal. 2 , 3 , 21 We observed that the LDF and PPGamp signals were usually correlated well (not shown). We also computed R, Tr, and Pr indices to pain, using the PPGamp signal, which showed no statistical differences compared with the indices obtained using the LDF ( Table S1 ).…”
Section: Supplementary Materialsmentioning
confidence: 82%
See 2 more Smart Citations
“…The height of the PPG pulses was extracted (photoplethysmograph amplitude [PPGamp]), followed by the same pre-processing steps for the LDF signal. 2 , 3 , 21 We observed that the LDF and PPGamp signals were usually correlated well (not shown). We also computed R, Tr, and Pr indices to pain, using the PPGamp signal, which showed no statistical differences compared with the indices obtained using the LDF ( Table S1 ).…”
Section: Supplementary Materialsmentioning
confidence: 82%
“…To overcome this limitation, we assumed we were obtaining another cycle of unique oscillatory response in every 10 seconds of blood flow. 3 , 19 Based on this effective unit of time, we would need another 40×10 seconds=400 seconds=~7 minutes of baseline data in addition to the length of the task stimulation to obtain bootstrap P -value with reasonable robustness and resolution. For this reason, we constructed the null distribution by combining the 5-minute silent baseline recording and 10–15 minutes of the extended baseline recording periods ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients that experience pathologies characterized by musculoskeletal ischemic injury, such as sickle cell disease, PVD, or complex regional pain syndrome (CRPS) often present both pain and altered autonomic vasomotor responses to tissue ischemia 36,57,58,59 . Our data suggests that muscle GDNF, combined with GFRα1 upregulation can sensitize muscle primary afferents after I/R.…”
Section: Clinical Significancementioning
confidence: 99%
“…BVP has been used to assess rapid stimuliinduced autonomic responses 16 , and is suitable for capturing an individual's acute physiological response to a pain-provoking stimulus. Specifically, a reduction in BVP amplitude from the baseline in response to a stimulus reflects peripheral vasoconstriction in the finger and is known to be associated with sympathetic arousal caused by acute stress 16,17 and thermal pain 18 . We thus used the constriction percentages of BVP amplitude after stimulus onset as an index of physiological pain response (see Methods for details).…”
mentioning
confidence: 99%